2017
DOI: 10.4236/ojfd.2017.74032
|View full text |Cite
|
Sign up to set email alerts
|

Decisive Parameters for Backwater Effects Caused by Floating Debris Jams

Abstract: The dimensional analysis of the backwater effect caused by debris jams results in the Froude number of the approach flow in the initial situation prior to debris jam formation and the debris density as decisive parameters. For the more precise detection of the influence of both parameters the results of different hydraulic model test series at the Laboratory of Hydraulic and Water Resources Engineering of the Technical University of Munich concerning debris jams at spillways as well as at racks for the retenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 5 publications
(3 reference statements)
2
14
0
Order By: Relevance
“…Schalko et al () used flume experiments to study the backwater effect of LW jams, finding that backwater rise depends mainly on the approach flow and LW jam porosity, the latter of which was significantly influenced by the percentage of fine organic material. Hartlieb () reported similar findings, but noted that backwater effect can vary significantly between different test runs with identical test conditions, due to the randomness of debris jam development. Clearly, additional research is warranted.…”
Section: Introductionsupporting
confidence: 90%
“…Schalko et al () used flume experiments to study the backwater effect of LW jams, finding that backwater rise depends mainly on the approach flow and LW jam porosity, the latter of which was significantly influenced by the percentage of fine organic material. Hartlieb () reported similar findings, but noted that backwater effect can vary significantly between different test runs with identical test conditions, due to the randomness of debris jam development. Clearly, additional research is warranted.…”
Section: Introductionsupporting
confidence: 90%
“…These studies concluded that the ratio of flow depth to LW diameter was key to determining whether LW stays in the reservoir or overtops the dam. The ratio of LW length to opening width is also a contributing factor as seen in sabo and slit dam experiments (Ishikawa and Mizuyama, 1988;Shrestha et al, 2012;Horiguchi et al, 2015;Chen et al, 2020). Recent experiments by Rossi and Armanini 2019, Meninno et al (2019), and Chen et al (2020) also explored the trapping efficacy of slits dams, without and eventually with upstream grills as suggested by Bezzola et al (2004).…”
Section: Introductionmentioning
confidence: 95%
“…These works have mostly focused on trapping efficacy and on defining relevant opening sizes and shapes to achieve the desired function. Numerical modelling of LW freely floating or interacting with structures emerged in the 2010s and is subject to constant improvement (Horiguchi et al, 2015;Kimura and Kitazono, 2019;Ruiz-Villanueva et al, 2014a;Shrestha et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schalko, Schmocker, Weitbrecht, and Boes () recently carried out laboratory experiments on wood accumulation at a retention structure in the form of a rack (or spillway;e.g., Hartlieb, ); however, an analogy can be found between the distance between piers or between a pier and a bank and the distance between the cylindrical elements of the rack. The tests primarily illustrated how backwater effects changed according to wood accumulation over time; during the first phase of jam formation, the backwater rise was faster and larger as soon as the logs spanned the entire rack, the upcoming logs formed a debris carpet, and the effect on the backwater rise was minor.…”
Section: Factors Influencing Wood Accumulation At Bridges: Main Findimentioning
confidence: 99%